Effects of dehydroepiandrosterone supplementation on women with poor ovarian response: A preliminary report and review - Kuan-Hao Tsui; Li-Te Lin; Renin Chang; Ben-Shian Huang; Jiin-Tsuey Cheng; Peng-Hui Wang (Elsevier, 2015)
Objective: To investigate the effect of dehydroepiandrosterone (DHEA) supplementation on women with poor ovarian response (POR). Materials and methods: Women with POR treated with flexible daily gonadotropin-releasing hormone antagonist in vitro fertilization (IVF) cycles at The Reproductive Center in Kaohsiung Veterans General Hospital between January 2013 and October 2013, were enrolled for this prospective study. When patients failed to become pregnant during the first IVF cycle, they were treated with DHEA supplementation (30 mg, 3 times a day, orally) for 3 months (mean 12.2 weeks) before the next IVF cycle. Parameters of biochemical, ultrasound and treatment outcomes were compared before and after DHEA supplementation. Results: Ten patients with a mean age of 36.6 ± 4.2 years were identified. After DHEA treatment, there was a significant increase in antral follicle count, from 2.8 ± 1.0 to 4.1 ± 1.2 (p < 0.05), and anti-Müllerian hormone, from 0.4 ± 0.2 ng/mL to 0.84 ± 0.2 ng/mL (p < 0.001). A significant decrease of Day 3 follicle-stimulating hormone and estradiol, from 14.4 ± 1.7 mIU/mL to 10.1 ± 0.7 mIU/mL and from 51.2 ± 6.3 pg/mL to 35.2 ± 4.2 pg/mL, respectively (both p < 0.001), was noted. Increased numbers of retrieved oocytes (from 2.4 ± 1.1 to 4.2 ± 1.2; p < 0.01), fertilized oocytes (from 1.7 ± 0.5 to 3.8 ± 1.1; p < 0.001), Day 3 embryos (from 1.7 ± 0.5 to 3.7 ± 1.1; p < 0.001) and transferred embryos (from 1.7 ± 0.8 to 2.8 ± 0.8; p < 0.01) were also seen in these women with POR after DHEA treatment. Three women became pregnant after DHEA treatment. Conclusion: The potential benefits of DHEA supplementation in women with POR were suggested by the biochemical parameters and IVF outcomes.